Pengaruh Motivasi dan Self-Efficacy terhadap Kepuasan Kerja Pegawai Bagian Prokompim Sekretariat Daerah Kabupaten Pekalongan - Alviatun Karimah; Chalimah Chalimah (Jurnal Simki Economic, 2025)
This research aims to analyze the influence of motivation and self-efficacy on employee job satisfaction in the Prokompim section of the Regional Secretariat of Pekalongan Regency. The method used is a quantitative approach with multiple linear regression analysis. Data collection was carried out through questionnaires distributed to employees of the Prokompim department, both with ASN and non-ASN status, with a sample of 30 respondents and the data was processed using SPSS version 20. The results of this research are that motivation has a positive and significant effect on employee job satisfaction, while self -efficacy has a positive and insignificant effect on job satisfaction. These findings can be a basis for management in formulating human resource development strategies in government environments.